Principles of Mössbauer Spectroscopy - Gibb, Terence (Dordrecht Springer Netherlands, 1976)
The emergence of Mossbauer spectroscopy as an important experi mental technique for the study of solids has resulted in a wide range of applications in chemistry, physics, metallurgy and biophysics. This book is intended to summarize the elementary principles of the technique at a level appropriate to the advanced student or experienced chemist requiring a moderately comprehensive but basically non-mathematical introduction. Thus the major part of the book is concerned with the practical applications of Mossbauer spectroscopy, using carefully selected examples to illustrate the concepts. The references cited and the bibliography are intended to provide a bridge to the main literature for those who subseouent ly require a deeper knowledge. The text is complementary to the longer research monograph, 'Mossbauer Spectroscopy', which was written a few years ago in co-authorship with Professor N.N. Greenwood, and to whom I am deeply indebted for reading the preliminary draft of the present volume. I also wish to thank my many colleagues over the past ten years, and in particular Dr. R. Greatrex, for the many stimu lating discussions which we have had together. However my greatest debt is to my wife, who not only had to tolerate my eccen tricities during the gestation period, but being a chemist herself was also able to provide much useful criticism of the penultima te draft
References -- 10 Impurity and Decay After-effect Studies -- 10.1 Impurity doping -- 10.2 Decay after-effects -- References -- 11 Biological Systems -- 11.1 Haemoproteins -- 11.2 Ferredoxins -- References -- Observed Mossbauer Resonances
Keywords: Humanities and Social Sciences; Humanities; Social sciences